2004
DOI: 10.3758/bf03194882
|View full text |Cite
|
Sign up to set email alerts
|

Time perception with and without a concurrent nontemporal task

Abstract: Prospective time estimates were obtained from human subjects for stimulus durations ranging from 2 to 23 sec. Presence and absence of a concurrent nontemporal task was manipulated within subjects in three experiments. In addition, location of the task within temporal reproduction trials and psychophysical method were varied between groups in Experiments 2 and 3, respectively. For long-duration stimuli, the results of all three experiments conformed to results in the literature, showing a decrease in perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…This proposition can be investigated by trying to "repair" the deficient informational basis upon which duration reproduction draws after the stimulus interval. With regard to long stimulus intervals (lasting several seconds or even minutes), at least, it is assumed that the accuracy of duration reproduction depends not only on the encoding conditions during the stimulus interval, but also on the conditions under which the duration is reproduced (Hemmes, Brown, & Kladopoulos, 2004). In the present experiment, the duration of the stimulus interval was reproduced under two different conditions.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…This proposition can be investigated by trying to "repair" the deficient informational basis upon which duration reproduction draws after the stimulus interval. With regard to long stimulus intervals (lasting several seconds or even minutes), at least, it is assumed that the accuracy of duration reproduction depends not only on the encoding conditions during the stimulus interval, but also on the conditions under which the duration is reproduced (Hemmes, Brown, & Kladopoulos, 2004). In the present experiment, the duration of the stimulus interval was reproduced under two different conditions.…”
Section: Methodsmentioning
confidence: 82%
“…However, it was also demonstrated that the accuracy of duration reproduction was not exclusively a function of the encoding activity but was also influenced by the support provided for the reconstruction process itself (for a related result, see Hemmes et al, 2004). The two influences seemed to be independent of each other, since there was no significant interaction between coordinative demands and the context information factor.…”
Section: Discussionmentioning
confidence: 92%
“…The involvement of attention mechanisms is a fundamental issue in contemporary research on timing and time perception (Brown & Boltz, 2002;Buhusi & Meck, 2009;Burle & Casini, 2001;Hemmes, Brown, & Kladopoulos, 2004). Although the variability of estimates is sometimes argued to depend on attention, the role of attention is most commonly used for explaining the perceived duration of involving, for instance, a series of partially overlapping visual displays marking intervals of different lengths that had to be timed for eventual reproduction.…”
Section: Attentionmentioning
confidence: 99%
“…The influence of attention on time perception has been reported for a wide range of durations and using different temporal tasks, such as time estimation, time production, and time reproduction (Brown, 1985(Brown, , 1997(Brown, , 2008Hemmes, Brown, & Kladopoulos, 2004). For instance, when participants are engaged in a time reproduction task together with a concurrent nontemporal task, their temporal estimates are generally less accurate than temporal estimates obtained without the concurrent task (Zakay & Block, 2004).…”
mentioning
confidence: 99%
“…To investigate the role of attentional resources in time perception, previous studies have added a concurrent task to the temporal one [e.g., reading (visual) tasks (Brown, 1997;Hemmes et al, 2004;Mioni, Stablum, McClintock, & Grondin, 2014;Rakitin, Stern, & Malapani, 2005); articulatory suppression (auditory) tasks (Delgado & Droit-Volet, 2007;Droit-Volet & Clément, 2005;Droit-Volet & Rattat, 2007; see also Rattat & Droit-Volet, 2012), or visuo-auditory tasks (Berry, Li, Lin, & Lustig, 2014)]. …”
mentioning
confidence: 99%